Things we hide from the light [large type] - Score, Lucy (Score, Lucy. Knockemout series ;, 2023)
"Nash Morgan was always known as the good Morgan brother, with a smile and a wink for everyone. But now, this chief of police is recovering from being shot and his Southern charm has been overshadowed by panic attacks and nightmares. He feels like a brooding shell of the man he once was. Nash isn't about to let anyone in his life know he's struggling. But his new next-door neighbor, smart and sexy Lina, sees his shadows. As a rule, she's not a fan of physical contact unless she initiates it, but for some reason Nash's touch is different. He feels it too. The physical connection between them is incendiary, grounding him and making her wonder if exploring it is worth the risk. Too bad Lina's got secrets of her own, and if Nash finds out the real reason she's in town, he'll never forgive her. Besides, she doesn't do relationships. Ever. A hot, short-term fling with a local cop? Absolutely. Sign her up. A relationship with a man who expects her to plant roots? No freaking way. Once she gets what she's after, she has no intention of sticking around. But Knockemout has a way of getting under people's skin. And once Nash decides to make Lina his, he's not about to be dissuaded . . . even if it means facing the danger that nearly killed him."--